To Do No Harm: Humanitarian Aid in Conflict Demands Political Engagement. (19th January 2018) - Patel, Ronak B.; Wild, Hannah B.
Abstract: Humanitarian aid in settings of conflict has always been fraught with challenges. In the absence of political engagement, however, manipulation by state authorities, however, have the potential to pervert aid intervention to inflict harm. South Sudan exemplifies how states may abuse the humanitarian response to retreat from public responsibility, divert funds to further violence and conflict and dictate the distribution of aid. Recent trends toward nationalist policies in the West that favor disengagement and limited military strikes have the very effect of allowing this abuse to transform humanitarian aid into a tool for harm. ( Disaster Med Public Health Preparedness . 2018;12:567–568)